2020
DOI: 10.1371/journal.pone.0233290
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming collinearity in path analysis of soybean [Glycine max (L.) Merr.] grain oil content

Abstract: Path analysis allows understanding the direct and indirect effects among traits. Multicollinearity in correlation matrices may cause a bias in path analysis estimates. This study aimed to: a) understand the correlation among soybean traits and estimate their direct and indirect effects on gain oil content; b) verify the efficiency of ridge path analysis and trait culling to overcome colinearity. Three different matrices with different levels of collinearity were obtained by trait culling. Ridge path analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…For NG, Ghiday et al 30 reported a heritability of 0.98. Similarly, Del Conte et al 31 and de Albuquerque et al 32 reported heritability estimates of 0.70 and 0.59, respectively. For HGW, Bisinotto et al 33 , reported a heritability estimate of 0.77 using 31 lines from a breeding program.…”
Section: Genetic Parametersmentioning
confidence: 89%
See 1 more Smart Citation
“…For NG, Ghiday et al 30 reported a heritability of 0.98. Similarly, Del Conte et al 31 and de Albuquerque et al 32 reported heritability estimates of 0.70 and 0.59, respectively. For HGW, Bisinotto et al 33 , reported a heritability estimate of 0.77 using 31 lines from a breeding program.…”
Section: Genetic Parametersmentioning
confidence: 89%
“…The genomic correlation estimates were consistent with those found in the literature. According to Del Conte et al 31 and Li et al 34 , the genetic correlation estimates between NP and NG were 0.87 and 0.88, respectively.…”
Section: Genetic Parametersmentioning
confidence: 95%
“…Assessing genetic variability present in germplasm using morphological traits by multivariate analysis and understanding the associations between seed yield and yield-related traits would facilitate the selection of progenies through breeding cycles. This was studied earlier in blackgram [16,17] and soybean [18,19].…”
Section: Introductionmentioning
confidence: 88%
“…Although the correlation study between variables is a great tool in plant breeding programs, the study does not allow to observe the effect that a variable provides on the other, making the correlation coefficients unfeasible in indicating variables for indirect selection as they do not take into account the causes and effects of this association (Del Conte et al., 2020). To overcome this problem, Wright (1921) developed a method called a path analysis, which allows the dissociation of the correlation coefficients in the direct effect (DE) and indirect effect (IE) of a group of independent variables on a main dependent variable.…”
Section: Introductionmentioning
confidence: 99%